PENERAPAN STRUKTUR DAN HARMON STORY CIRCLE PADA PENULISAN SKENARIO FILM “GETIR” - Pande Ayur Sawitar Kumari; I Komang Arba Wirawan; I Nyoman Payuyasa (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
The film “Getir” tells the story of a Balinese woman who is in an inharmonious marriage due to an extramarital affair. In the process of writing the screenplay, this film applies the story structure of Dan Harmon Story Circle. Dan Harmon Story Circle is an alternative story structure with a characteristic that divides the story into eight stages experienced by the main character. The application of this story structure aims to highlight the changes that occur in the main character. This can be seen from the comparison of conditions at the beginning of the story starting to the end of the story. The scenario preparation process uses a method consisting of the preparation stage and the cultivation stage. The preparation stage starts from determining the idea, theme, story target to the plot. The stages of cultivation are carried out by compiling the premise, synopsis, character profile, writing treatment, to the scenario. In the process of writing the screenplay, the writer uses several theories to develop the scenario. The theories that the author uses are Elizabeth Lutter's Scriptwriting theory, Narrative, Dan Harmon Story Circle structure, and Stage of Grief. “Getir“ film scenario consists of 22 scenes, genre drama with a story duration of 20 minutes, taking the setting of the story in several places such as houses and traditional markets.